Detection threshold and sensory preference for salty taste among Malay, Chinese and Indian students in Health Campus, Universiti Sains Malaysia - Marina A.M.; Nurul Husna A.R.; Ruhaya H. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Most dietary sodium is consumed as common salt (sodium chloride). However, high consumption of salt is highly related to several health problems such as hypertension, stroke and cardiovascular disease. The consumption of salt is related to individuals’ detection threshold and preference for salty taste. Thus, this study was carried out to determine the detection threshold and sensory preference for salty taste among Malay, Chinese and Indian undergraduate students in Health Campus, Universiti Sains Malaysia. Ninety students from three ethnic groups (Malay, Chinese and Indian) were conveniently selected as panelists in this study. Detection threshold for salty taste was conducted using three-alternative force choice (3-AFC) method. Sensory preference test was conducted using a 9 point hedonic scale for saltiness in vegetable soup. Salt detection threshold for Malay, Chinese and Indian students were 1.56, 1.19 and 0.90 mM, respectively, but no significant difference was found among ethnics. Across gender, the lowest salt detection threshold was found in Indian females (0.74 mM) and Chinese males (0.70 mM). Chinese and Indian students showed a decreasing trend in salt preference as salt concentration was increased in vegetable soup. Malay students, however, demonstrated a more fluctuate trend across increasing salt concentration, with 0.5 mM as the most preferred salt concentration. Malay and Chinese male students had higher preference for saltiness compared to their females’ counterpart. No relationship was found between salt detection threshold and preference for saltiness among Malay, Chinese and Indian students.